Impact of noise on health. Measures to control excessive traffic noise levels - van Keulen, Wim (Education and Research in Health Sciences, 2023)
Long-standing research has shown that noise pollution has harmful consequences on human health. Environmental noise is becoming a significant problem in most nations. The spread of undesired noises into the environment is known as noise pollution. We are virtually constantly surrounded by noise. Environmental noise causes an illness burden that is second only to the air pollution-related disease burden in terms of scale. Due to noise from roads, trains, and airports, one in three persons is annoyed during the day and one in five has sleep disturbances at night.Noise exposure may have both a direct and an indirect impact on one's physical health. In extreme circumstances, loud noises might really harm your hearing. In addition to severely harming human health, this excessive noise prevents individuals from going about their everyday lives at home, at work, at school, and in their free time. Chronic exposure to environmental noise has a considerable negative impact on both physical and mental health.The most common source of environmental noise and the main factor in the overall negative impact of noise on health is road traffic noise. The most popular technique for noise reduction, if noise mitigation is determined to be practical and appropriate, is the application of noise barriers. However, out of the several technologies available to road authorities, the application of noise-reducing pavements is not only the most cost-effective but also can be implemented on short notice.
Keywords: noise; health; annoyance; traffic